2019
DOI: 10.3390/diagnostics9040149
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian Anomalies Prevalence Diagnosed by Hysteroscopy and Laparoscopy in Mexican Infertile Women: Results from a Cohort Study

Abstract: Background: To evaluate the prevalence of Müllerian anomalies (MAs) in a cohort of infertile Mexican women candidates for infertility treatments (intrauterine insemination or IVF (In vitro fertilization) cycles). Methods: We performed a retrospective observational study on a cohort of consecutive women, who underwent hysteroscopy and laparoscopy as part of the basic infertility workup from 2002 to 2014, at our center. Our aim was to calculate the prevalence of MAs and each subtype. Results: A total of 4005 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Barton SE and Coworkers have reported in their study that the TVUS follicular aspiration was preferable as procedure requiring less time and invasivess, compared to the TAUS which could be considered a safer and useful technique for oocyte retrieval in cases of inaccessible ovaries by the transvaginal approach [26]. In fact, literature data report that the TAUS approach is able to maximize the number of oocytes retrieved, mainly in women with radical hysterectomies, transposed ovaries [27,28], Müllerian agenesis [29] as well as in cases of increased body mass index (BMI) for which the poor ultrasound image quality, make the ovaries unreachable [30,31]. However, despite the feasibility of this approach, the TAUS retrieval, often requiring multiple punctures for each ovary impacting on patients' discomfort and the infectious risk [17], makes preferable the transvaginal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Barton SE and Coworkers have reported in their study that the TVUS follicular aspiration was preferable as procedure requiring less time and invasivess, compared to the TAUS which could be considered a safer and useful technique for oocyte retrieval in cases of inaccessible ovaries by the transvaginal approach [26]. In fact, literature data report that the TAUS approach is able to maximize the number of oocytes retrieved, mainly in women with radical hysterectomies, transposed ovaries [27,28], Müllerian agenesis [29] as well as in cases of increased body mass index (BMI) for which the poor ultrasound image quality, make the ovaries unreachable [30,31]. However, despite the feasibility of this approach, the TAUS retrieval, often requiring multiple punctures for each ovary impacting on patients' discomfort and the infectious risk [17], makes preferable the transvaginal approach.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of mullerian duct anomalies also dif-fers significantly, with findings ranging from 0.16-10% [26,27]. They were either congenital mullerian anomalies (U1, U2, U3) or acquired lesions like endometritis, polyps, adhesions or combined lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of two retrospective studies performed on a large number of patients (4005 and 3811 women, respectively) showed a prevalence of Müllerian abnormalities between 4.4 and 7.5%. The distribution of malformations reported varies 54.2-54.9% for septate uterus, 14.2-15.8% for arched uterus, 10.2-10.7% for bicornuate uterus, 5.8-8.5% for unicorn uterus and 3.4-6.5% for hypoplasia/agenesis [59,60].…”
Section: How Can Hl Manage Uterine Malformations?mentioning
confidence: 99%